Taking it to the street : an examination of the flash mob phenomenon : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Visual and Material Culture at Massey University, Wellington, New Zealand - Pierce, Leith (Massey University, 2012)
In little less than a decade, ʻflash mobʼ has become an internationally recognised phrase. What began in 2003 as a short-lived collection of personal experiments (Wasik, 2010), quickly flourished. Flash mobs include a wide spectrum of public performances that share some bizarre features. As events, they begin without warning and end as abruptly; the rationale for their fleeting existence is seemingly unexplainable, confounding accepted performer and audience roles. This thesis constructs a timeline of preceding performative practices linked to elements of the flash mob. These practices are as diverse as Ancient Greek theatrical spectacle, the Surrealist manifesto, and Happenings of the 1960s, which protested against an alternative spectacle, the spectacle of capitalist society. Applying viewing practices that first arose in the nineteenth centuryʼs early modern consumerist era illuminates features of the contemporary flash mob. The identity of flash mob participants is analysed through employing object-relation theories of material culture. Mobile communicative devices are integral technological tools that feature prominently in examining the process of the flash mob (Rheingold, 2000, 2003; Lanier, 2011). These communication tools, particularly with the advent of Internet based social media websites, provide opportunities to control the production process within a global context. This possibility is explored utilising the Frankfurt Schoolʼs debates surrounding the ability to meaningfully democratise a pervasive economic system. It is a parallel phenomenon of which advertisers and political activists alike have taken advantage. Exploiting the potential of the flash mob for such purposes has resulted in notable transformations. Though above all else, central to each expression of the flash mob, is the principle of the unexpected. Inexplicable surprise or punctum (Barthes, 2000) is presented herein as common purpose of these professed ʻpointless actsʼ (OED, 2008). While flash mobs continually aspire to confuse, this thesis arrives at underlying motivations centred upon the consistently applicable feature of surprise prevalent in theoretical case studies.
Keywords: Street performance; Flash mob